The Troubled Encounter Between Postcolonialism and African History - Zeleza, Paul (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 2006)
AbstractThis paper examines the complex engagements between what it calls the “posts” – poststructuralism, postmodernism and postcolonialism – and African studies. Specifically, it analyzes the analytical connections and contestations between postcolonial theory and African historiography. The paper interrogates some of the key ideas and preoccupations of both postcolonialism and historiography and explores the intersections between them. It is argued that the ambivalence and sometimes antagonism to postcolonialism by many African scholars is largely driven by ideological and ethical imperatives, while the troubled encounter between African history and postcolonialism is rooted in apparent intellectual and epistemic incongruities. Linking the two is the powerful hold of what I call nationalist humanism in the African imaginary, the nationalist preoccupations of African intellectuals, and the nationalist proclivities of African historiography. Productive engagement between African history and postcolonialism is of course possible, but it requires mutual accommodation, the incorporation in postcolonial studies of the insights developed in African historiography, and within the latter of some of the constructive interventions of postcolonial theory. Ultimately, however, I believe postcolonialism has serious limits in its methodological and conceptual capacities to advance what I would call the historic agendas of African historiography.